Factors influencing researchers' journal selection decisions. (June 2022) - Rowley, Jennifer; Sbaffi, Laura; Sugden, Martin; Gilbert, Anna
The scholarly publication landscape continues to grow in complexity, presenting researchers with ever-increasing dilemmas regarding journal choice. However, research into the decision-making processes associated with journal choice is limited. This article contributes by reporting on an international survey of researchers in various disciplines and with varying levels of experience. The study examines the extent to which various journal characteristics affect journal selection, perceptions of the extent to which university and national research policies impact on their journal choice, and the influence of academics' familiarity, confidence and objectives on journal choice. The most important factors influencing journal choice were as follows: reliability of reviewing, usefulness of reviewers' feedback, the reputation of the journal and confidence that their article is in scope for the journal. Publishing productivity, publishing experience, researcher role and discipline had little impact on the ranking of journal choice factors, suggesting that the research community is homogeneous.